Clinical evaluation of fenestration decompression combined with secondary curettage for ameloblastoma of the jaw: retrospective radiographic analysis - Kailiu Wu; Hao Luo; Zhuang Yuan; Yanan Wang; Xing Qin; Jie He (BMC Oral Health, 2022)
Abstract Background Ameloblastoma is a benign odontogenic epithelial tumor with local infiltration and a high recurrence rate that occurs most frequently in the jawbone. The aim of this study was to investigate the outcomes of fenestration decompression combined with secondary curettage (FDSC) in the surgical treatment of jaw ameloblastoma, and clarify the possibility of FDSC to become an appropriate therapeutic method for ameloblastoma with large lesion. Methods A retrospective analysis was carried out in 145 patients diagnosed with multicystic ameloblastoma (MA) and 88 patients with unicystic ameloblastoma (UA). These patients were divided into two groups based on the therapeutic regimen: the FDSC group and the local curettage (LC) group. Panoramic radiography was taken 2 years after curettage to evaluate the change in lesion area in each case, and the therapeutic effects of different treatment methods were further assessed by the chi square test. Results For MA, the effective rate of cystic cavity area reduction in the FDSC group (71.19%) was higher than that in the LC group (30.23%) (P < 0.001). For UA patients, the effective rate of lesion area reduction after FDSC was 93.02%, which was higher than that after LC (53.33%) (P < 0.001). Moreover, the recurrence rate of the FDSC group in the MA was 30.51%, which was significantly different from that of the LC group (P < 0.001). Regarding UA, the recurrence rates were 13.95% and 28.89%, after FDSC and LC, respectively, with no significant differences between the two groups (P > 0.05). Conclusions FDSC exhibits a much better curative effect than LC in both MA and UA, whereas the recurrence rate of these two therapeutic strategies did not significantly differ in UA. The above data demonstrated that FDSC may serve as a routine, safe, effective and appropriate surgical treatment plan for MA or UA patients with large lesions.